Influence of Brand Ambassadors and Social Media on Purchase Intention in Beauty Industry through Brand Image - Dinni Kurnianti; Ely Siswanto; Titis Shinta Dhewi (International Journal of Economics and Management Sciences, 2025)
The beauty industry is experiencing significant growth due to digital transformation, particularly through the use of brand ambassadors and social media marketing. This study investigates the impact of brand ambassadors and social media marketing on purchase intention, with brand image as the mediating variable. This research focuses on Azarine, the skincare from Indonesia and targets potential consumers in Riau Islands aged 18-44 who follow the Instagram account @azarinecosmeticofficial and recognize Prilly Latuconsina, Syifa Hadju, Angga Yunanda, and Lee Min Ho as brand ambassadors. A quantitative approach was applied using Structural Equation Modeling (SEM) with SmartPLS software. The research shows that brand ambassadors and social media marketing positively and significantly influence purchase intentions, with a higher direct impact compared to an indirect one through brand image. This study highlights the effectiveness of digital brand strategies in shaping consumer decisions and offers insights for marketing professionals in the beauty sector. These results emphasize the strategic role of celebrity endorsements and content-based engagement in influencing consumer perceptions and purchasing behavior.